THE DESIRABLE CHARACTERISTICS OF GRADUATES OF BACHELOR OF EDUCATION PROGRAM IN SOCIAL STUDIES AT RAJABHAT UNIVERSITY - Nualhom, Wanlee; Thongkam, Suthida; Prapasanobol, Vatcharaporn; Wanakool, Duangduen; Nillapun, Maream (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The objectives of this research were 1) to study the level of opinions about the desirable characteristics of graduate students of the faculty of education, and 2) to explore opinions about the desirable characteristics of graduate students from graduate producers, graduate users, and academics. The researchers used a questionnaire to collect data from students of Bachelor of Education in social studies and interviewed with graduate users, graduate producers, and academics. The statistics used for data analysis were percentage, mean, and standard deviation. The results of the research revealed that the overall opinion level was at a high level. The highest score is in the area of being a good person with morals and ethics and the teaching profession. The aspect with the least level of opinions was to be an innovator. Therefore, graduate producers should promote the characteristics of the graduates to heighten their innovation capability through well-planned instruction and extra activities followed by the Thailand qualification framework and professional standards of the Teachers Council of Thailand.